Impact of image guided fine needle aspiration cytology in diagnosis of pediatric hepatic mass and cytohistologic concordance - Chhanda Das; Madhumita Mukhopadhyay; Moumita Sengupta; Ashis Kumar Saha; Biswanath Mukhopadhyay (Wolters Kluwer Medknow Publications, 2014)
Background: Pediatric hepatic mass is a heterogeneous group of benign and malignant lesions. Percutaneous fine needle aspiration cytology (FNAC) can be utilized as a diagnostic modality to assess the nature of radiologically demonstrated hepatic lesions and thus facilitate individualized treatment. Aims and Objective: The objective of the present study was to determine the diagnostic accuracy of percutaneous FNAC of pediatric liver masses, a procedure that is less invasive than open biopsy. Materials and Methods: A prospective, observational study was carried out in the Department of Pathology in collaboration with Department of Pediatric surgery and Radio-diagnosis including 31 pediatric patients presenting over last two years (June 2011 to May 2013) with focal hepatic lesion on ultrasound and computed tomography (CT) scan. FNAC was carried out under image guidance and cytodiagnosis was reached after appropriate staining. By comparing with histopathology reports, diagnostic accuracy of cytology was evaluated. Result: Among 31 cases included in the study, 51.6% cases were cytologically benign and hemangioma was the most common benign lesion. Hepatoblastoma was the most accounted malignant tumour (12.9%). FNAC provided 94% sensitivity and 92% specificity in diagnosing benign and malignant tumours. Overall diagnostic accuracy was 93.10%. No significant complication was noted. Conclusion: Percutaneous FNAC under image guidance is an effective diagnostic tool for diagnosis of primary and metastatic tumours of liver in pediatric patients.